2020
DOI: 10.1101/2020.03.26.20044768
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Persistent SARS-CoV-2 presence is companied with defects in adaptive immune system in non-severe COVID-19 patients

Abstract: Defects in adaptive immune system, including reduced T cells and B cells, were frequently observed in non-severe COVID-19 patients with persistent SARS-CoV-2 shedding. Assessment of immune system could be clinically relevant for discharge management. AbstractBackground: COVID-19 has been widely spreading. We aim to examine adaptive immune cells in non-severe patients with persistent SARS-CoV-2 shedding.Methods 37 non-severe patients with persistent SARS-CoV-2 presence transferred to Zhongnan hospital of Wuhan … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 29 publications
0
28
0
2
Order By: Relevance
“…On the other hand, studying CD8 + T cells subsets, as the main effector cells in the direct killing of viral infected cells, can be helpful in determining the relative significance of T cell subsets and cellular immunity in the defensce against COVID-19 and its immunopathology [ 121 ]. Accordingly, similar to the acute phase of SARS and MERS diseases, COVID-19 patients with severe symptoms exhibit an extreme decline in total CD4+ and CD8 + T cells in their circulation [ 122 ], while patients with mild symptoms have normal to slightly higher T cell counts [ 123 ]. This decrease in T cells is likely to be caused by high levels of pro-inflammatory cytokines such as IL-6, IFN-I, and TNF-α in peripheral blood [ 71 , 82 ].…”
Section: Immune System Biomarkersmentioning
confidence: 99%
“…On the other hand, studying CD8 + T cells subsets, as the main effector cells in the direct killing of viral infected cells, can be helpful in determining the relative significance of T cell subsets and cellular immunity in the defensce against COVID-19 and its immunopathology [ 121 ]. Accordingly, similar to the acute phase of SARS and MERS diseases, COVID-19 patients with severe symptoms exhibit an extreme decline in total CD4+ and CD8 + T cells in their circulation [ 122 ], while patients with mild symptoms have normal to slightly higher T cell counts [ 123 ]. This decrease in T cells is likely to be caused by high levels of pro-inflammatory cytokines such as IL-6, IFN-I, and TNF-α in peripheral blood [ 71 , 82 ].…”
Section: Immune System Biomarkersmentioning
confidence: 99%
“…Viral and immunopathological studies revealed distinct patterns between mild and severe or critical forms of COVID-19 4,[17][18][19][20][21][22][23][24][25] . Both severe and critically ill patients displayed higher viral load in the upper respiratory tract than mild cases, together with delayed clearance overtime 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Both severe and critically ill patients displayed higher viral load in the upper respiratory tract than mild cases, together with delayed clearance overtime 17,18 . Likewise, they presented with lymphopenia due to a decrease in CD4+ and CD8+ T cells, as well as T cells exhaustion accompanied by a marked inflammatory response [20][21][22][23][24][25] . Pro-and anti-inflammatory cytokines and chemokines concentrations were increased systemically and locally in the lung and correlated with severity [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…Viral and immunopathological studies revealed distinct patterns between mild and severe or critical forms of COVID-19 [4,5,9,[21][22][23][24][25][26][27]. Both severe and critically ill patients displayed higher viral load in the upper respiratory tract than mild cases, together with delayed clearance overtime [21,22].…”
mentioning
confidence: 98%
“…Both severe and critically ill patients displayed higher viral load in the upper respiratory tract than mild cases, together with delayed clearance overtime [21,22]. Likewise, they presented with lymphopenia due to a decrease in CD4+ and CD8+ T cells, as well as T cell exhaustion accompanied by a marked inflammatory response [5,9,[24][25][26][27]. Pro-and anti-inflammatory cytokines and chemokine concentrations were increased systemically and locally in the lung and correlated with severity [5,9,24].…”
mentioning
confidence: 99%